CG7630 is the Drosophila melanogaster homolog of the cytochrome c oxidase subunit COX7B. (14th June 2022) - Brischigliaro, Michele; Cabrera‐Orefice, Alfredo; Sturlese, Mattia; Elurbe, Dei M; Frigo, Elena; Fernandez‐Vizarra, Erika; Moro, Stefano; Huynen, Martijn A; Arnold, Susanne; Viscomi, Carlo; Zeviani, Massimo
Abstract: The mitochondrial respiratory chain (MRC) is composed of four multiheteromeric enzyme complexes. According to the endosymbiotic origin of mitochondria, eukaryotic MRC derives from ancestral proteobacterial respiratory structures consisting of a minimal set of complexes formed by a few subunits associated with redox prosthetic groups. These enzymes, which are the "core" redox centers of respiration, acquired additional subunits, and increased their complexity throughout evolution. Cytochrome c oxidase (COX), the terminal component of MRC, has a highly interspecific heterogeneous composition. Mammalian COX consists of 14 different polypeptides, of which COX7B is considered the evolutionarily youngest subunit. We applied proteomic, biochemical, and genetic approaches to investigate the COX composition in the invertebrate model Drosophila melanogaster . We identified and characterized a novel subunit which is widely different in amino acid sequence, but similar in secondary and tertiary structures to COX7B, and provided evidence that this object is in fact replacing the latter subunit in virtually all protostome invertebrates. These results demonstrate that although individual structures may differ the composition of COX is functionally conserved between vertebrate and invertebrate species. Synopsis: The mitochondrial cytochrome c oxidase subunit COX7B was thought to be mammalian specific. This study reveals that the evolutionarily divergent protein CG7630 is the functional ortholog of COX7B in Drosophila melanogaster . CG7630 is a structural component of COX in D. melanogaster . Despite poor sequence similarity, CG7630 functionally corresponds to COX7B. Invertebrate and mammalian COX enzymes have the same number of subunits. The existence of CG7630 demonstrates divergent evolution of COX subunits in vertebrates and invertebrates. Abstract : The mitochondrial cytochrome c oxidase subunit COX7B was thought to be mammalian specific. This study reveals that the evolutionarily divergent protein CG7630 is the functional ortholog of COX7B in Drosophila melanogaster .